New documents on 18th century murcia typography - García Cuadrado, Amparo (Revista General de Información y Documentación, 2012)
In June 1788 the printers Manuel Muñiz and Antonio de Santa María set up to create a joint printing press reported as the first one to be established in Murcia city. One month later, they registered it at Francisco Bocio’s record office in order to formalize this partnership and establish the conditions for its management. The information from this documentation together with other literature about the story of the Plano de San Francisco street printing shop cast light on a 18th century murcian press history section.